Struktur Organisasi, Budaya Organisasi, Dan Kualitas Laporan Keuangan Pemerintah Daerah - Handoko A. Hasthoro; Henry Sarnowo (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2014)
This study tried to demonstrate empirically the factors that affect the quality of financial reports of local governments in Indonesia. Organizational structure and culture of the organization and will be used as a determinant and explanatory item for the quality of financial statements. The size of the organization, the number of regional working units, and the number of board members representing the local people used as a proxy for organizational structure. Organizational culture proxied by the quality of e-government implementation. The quality of local government financial reports using Government Audit Agency audit opinion as a proxy. Using multiple linear regression method, the results of the study with a sample of 184 Local Governments show that the organizational culture (e-government) has a positive effect on the quality of local government financial reports. Organizational structure’s variable which is organizational sizea nd the number of members of regional parliaments has no effect on the quality of local government financial reports. Variable number of regional working units has a negative effect on the quality of local government financial reports. Statistical results shows that the average (mean) quality of local government financial reports have not been good since the value is 2.804 which means that below the qualified opinion (value 3). Implication of this study is the local government must pay attention to the quality of financial reporting by implementing properly the standards required by way of education and can often be done through cooperation with universities.